STATE AND SUPPORT OF STRATEGIC PLANNING OF FOREIGN ECONOMIC ACTIVITY OF EU ENTERPRISES - KULISH, Damir (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the current state and support for strategic planning of foreign economic activity of EU enterprises. It is established that the European Union, or rather its member states, has the competence to harmonize legislation, which it implements in such areas as the free circulation of goods, services, capital, as well as in such sectors as agriculture, fishing, transport and energy. Meanwhile, health, tourism and civil protection are examples of areas where the European Union can only pass laws in support of member states ’ initiatives. The EU has a relatively open trade regime, which has stimulated the development of relations with a wide range of trading partners. Indeed, the EU is deeply integrated into global markets, and this picture can be expected to continue, as modern transport and communications developments create an additional incentive for producers to exchange goods (and services) around the world. Foreign economic activity is regulated independently or jointly at several levels: national; bilateral and regional; and global. Usually, national state bodies regulate foreign economic activity autonomously, issuing various laws, regulations, regulations, permits, and so on. Regional bodies of competence, such as the EU Council of ministers, the UN Security Council, etc., can also operate independently. Coordinated or joint regulation of foreign economic activity is carried out by issuing joint acts or signing international treaties and agreements, as well as in accordance with various rules and Customs adopted by intergovernmental or non-governmental bodies and organizations. Any regulation is aimed at implementing a particular foreign economic policy (the means of which we will explain in the next topic), and this contributes to economic integration into the world economy. On the other hand, the processes of foreign economic activity, increasingly complex relationships and the desire to quickly solve problems lead to an increase in the number and role of bodies and organizations in regulating foreign economic activity.